2008
DOI: 10.1038/sj.bdj.2008.319
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of mineral trioxide aggregate and formocresol as pulp medicaments for pulpotomies in primary molars

Abstract: • Mineral trioxide aggregate (MTA) was assessed in pulpotomised primary molars.• The clinical and radiographic success rate of MTA was recorded at 24 months follow-up.• This clinical trial study showed the success of white MTA in primary molars. I N B R I E F RESEARCHPurpose The aim of this study was to compare the effect of white mineral trioxide aggregate (MTA) to that of formocresol (FC) as pulp dressing agents in pulpotomised primary molars. Methods In this clinical trial study, 60 lower second primary mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
1
7

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 16 publications
2
41
1
7
Order By: Relevance
“…Also, the majority of human clinical investigations with which we compared our study results, used preformed stainless crowns. 5,23,24,27,28,32,34 In the radiographic analysis performed every 6 months no signs of displacement or resorption of the MTA was seen. None Based on the results obtained in the present investigation for both types of MTA we can verify that the success rates differ depending on the type of MTA: Grey MTA allowed higher clinical and radiographic success rates.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Also, the majority of human clinical investigations with which we compared our study results, used preformed stainless crowns. 5,23,24,27,28,32,34 In the radiographic analysis performed every 6 months no signs of displacement or resorption of the MTA was seen. None Based on the results obtained in the present investigation for both types of MTA we can verify that the success rates differ depending on the type of MTA: Grey MTA allowed higher clinical and radiographic success rates.…”
Section: Discussionmentioning
confidence: 95%
“…Dentine formation showed the presence of odontoblastic activity which demonstrated the root canal pulp vitality and the absence of pathology of the treated molars. 24,32 Comparing dentine bridge formation between the two types of MTA, globally, Grey MTA induced the formation of a higher number of dentine bridges. This difference was statistically significant (P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…47 Many studies have shown positive results for MTA when compared with formocresol. 48 Upon histological examination animal studies have shown superior results for MTA, white Portland cement (WPC), and beta-tricalcium phosphate (b-TCP) over formocresol and FS. 49 Other promising possibilities include enamel matrix derivative (EMD), a material that utilises active odontogenic protein.…”
Section: Opinionmentioning
confidence: 99%
“…2, 3 Although, in young permanent teeth, indirect and direct pulp capping techniques are an accepted procedure, but in primary teeth it is contraindicated because of possibility of undetected avascular microscopic pulp exposure.…”
mentioning
confidence: 99%